Wwox seletion in mouse B cells leads to genomic instability, neoplastic transformation, and monoclonal gammopathies - McBride, Kevin M. (2019)
WWOX (WW domain containing oxidoreductase) expression loss is common in various cancers and characteristic of poor prognosis. Deletions, translocations, and loss of expression affecting the WWOX gene are a common feature of various B cell neoplasms such as certain B cell lymphomas and multiple myeloma. However, the role of this common abnormality in B cell tumor initiation and/or progression has not been defined. In this study, we conditionally deleted Wwox early in B cell development by means of breeding Cd19-Cre transgenic mice crossed to Wwox floxed mice (Cd19 Wwox KO). We observed a significant reduced survival in Cd19 Wwox KO mice and the development of B cell neoplasms including B cell lymphomas, plasma cell neoplasias characterized by increased numbers of CD138+ populations as well as monoclonal gammopathies detected by serum protein electrophoresis. To investigate whether Wwox loss could play a role in genomic instability, we analyzed DNA repair functions during immunoglobulin class switch joining between DNA segments in antibody genes. While class switch recombination (CSR) was only slightly impaired, Wwox deficiency resulted in a dramatic shift of double strand break (DSB) repair from normal classical-NHEJ toward the microhomology-mediated alternative-NHEJ pathway, a pathway associated with chromosome translocations and genome instability. Consistent with this, Wwox deficiency resulted in a marked increase of spontaneous translocations during CSR. This work defines for the first time a role for Wwox for maintaining B cell genome stability during a process that can promote neoplastic transformation and monoclonal gammopathies.